Effects of Dexmedetomidine on Immune Cells: A Narrative Review - Chen, Rui; Sun, Yan; Lv, Jing; Dou, Xiaoke; Dai, Maosha; Sun, Shujun; Lin, Yun (Frontiers in Pharmacology, 2022)
As we all know, dexmedetomidine (DEX), as a highly selective α2 adrenergic receptor agonist, exerts sedative, anti-anxiety and hypnotic effects by inhibiting the discharge of norepinephrine neurons in locus coeruleus and GABA-related hypnotic pathways. However, the role of DEX in anti-inflammatory and immune regulation has gradually attracted the attention of researchers in recent years. The α2 adrenergic receptor is one of the members of the adrenergic receptor family, which is widely present in a variety of immune cells and mediates the biological behavior of the inflammatory immune system. At present, there have been more and more studies on the effects of DEX on immune cells and inflammatory responses, but few studies have systematically explored the anti-inflammatory and immunomodulatory effects of DEX. Here, we comprehensively review the published human and animal studies related to DEX, summarize the effects of DEX on immune cells and its role in related diseases, and propose potential research direction.